2019
DOI: 10.37268/mjphm/vol.19/no.2/art.171
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Lifestyle Factors as Determinants of Type 2 Diabetes Mellitus in Manado City, Indonesia

Abstract: High prevalence of diabetes mellitus is caused by various factors such as lifestyle changes and obesity, and tends to be higher in urban than in rural areas. The aim of this study was to analyse obesity, physical activity, smoking, and family history as determinants of type 2 diabetes mellitus in Manado City, Indonesia. A matched case-control study of outpatients at five public health centres in Manado City from February to November 2018 was conducted; cases were patients who had been clinically diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…When left unaddressed, this condition can result in persistent hyperglycemia, presenting substantial health hazards and potentially giving rise to severe complications. 6 These complications encompass a spectrum of issues spanning both macrovascular and microvascular domains, including peripheral vascular disease, nerve impairment, cardiovascular ailments, stroke, kidney dysfunction, diabetic retinopathy, and even the potential for blindness. 7 Previous research found that resident living with diabetes mellitus in the Lanjas subdistrict, highlights that the absence of a healthy lifestyle also poses a significant health challenge for those with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…When left unaddressed, this condition can result in persistent hyperglycemia, presenting substantial health hazards and potentially giving rise to severe complications. 6 These complications encompass a spectrum of issues spanning both macrovascular and microvascular domains, including peripheral vascular disease, nerve impairment, cardiovascular ailments, stroke, kidney dysfunction, diabetic retinopathy, and even the potential for blindness. 7 Previous research found that resident living with diabetes mellitus in the Lanjas subdistrict, highlights that the absence of a healthy lifestyle also poses a significant health challenge for those with diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%